TECHNART2023 - Non-destructive and Microanalytical Techniques in Art and Cultural Heritage - Manso, Marta (2023)
The first TECHNART conference was held in Lisbon in 2007 by the initiative of the Atomic Physics Center from the University of Lisbon, current Laboratory for Instrumentation, Biomedical Engineering and Radiation Physics (LIBPhys). The conference aimed to provide a cultural heritage science forum where the use of analytical techniques in art and cultural heritage were presented and discussed. After five editions held in different European cities and a hiatus of four years due to COVID, it is a privilege to welcome in 2023, once more in Lisbon, the TECHNART conference. The conference topics covers the application of a large range of analytical methods to art and cultural heritage investigations, namely X-ray analysis, confocal X-ray microscopy, synchrotron, ion beam and neutron-based techniques, FT-IR and Raman spectroscopy and microscopy, UV-Vis and NIR absorption/reflectance and fluorescence, laser-based analytical methods, magnetic resonance techniques, chromatography and mass spectrometry, optical and coherent imaging techniques, remote sensing and hyperspectral imaging. The TECHNART2023 program is organized in thematic sessions on analytical methods and their application to art and cultural heritage. Eight invited speakers will open thematic sessions on analytical methodologies, textiles, pigments and dyes, varnishes and resins, and metals. For four days, TECHNART2023 brings in over 180 oral communications in three parallel sessions and more than 260 posters distributed in four sessions. The abstracts from oral and poster communications are collected in this book. The conference accounts circa 400 participants representing around 50 countries from all over the world, offering an outstanding opportunity for exchanging knowledge and establishing new networks with other cultural heritage science researchers. TECHNART2023 results from the straight collaboration between LIBPhys and the other organizing institutions (NOVA School of Science and Technology, Faculdade de Ciências da Universidade de Lisboa, Universidade de Coimbra, Associação para o Desenvolvimento do Departamento de Física da Universidade de Coimbra) with the support from the TECHNART International Scientific Committee. It was equally important the partnership with Centro HERCULES, Museu Nacional do Azulejo, Microchemical Journal, and Journal of Cultural Heritage, as well as the participation of the commercial companies (HIROX Europe, OPUS instruments, NIREOS, BRUKER, FORENSCOPE) and the sponsoring of Heritage journal, Xpecam commercial company and the European X-ray Spectrometry Association (EXSA).